Analysis of Service Time in The Bank with Exponential Distribution - Mutiarasari, Yusna; Tirta, I Made; Pradjaningsih, Agustina (Jurusan Matematika FMIPA Universitas Jember, 2017)
Exponential distribution is general assumption to describe the distribution of service time for customer. To examine such assumption, the Goodness of Fit Test-Kolmogorov Smirnov is used. To know the condition queue system in BCA will be use some analyze the steady state characteristic measurement of work queue system on different day and hour.